Fenomena Entitlement Pada Generasi Y dan Z: Analisis Konteks dan Tanggapan Kritis-Konstruktif - Permatasari, Olga Sancaya Dyah (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2025)
Generation Y and Z are in the spotlight. One of the reasons is their tendency towards entitlement, namely expecting their personal needs to be prioritized without paying attention to and caring about the needs of others, not respecting ethics and social norms, and forgetting responsibility as part of society. However it could be the case that this entitlement attitude occurs because of a lack of proper understanding between awareness of the rights of responsible individuals and attitudes that reflect entitlement. This entitlement attitude could have its roots in liberalism and postmodernism, and was affected by technological developments, including social media. In an increasingly fluid world condition, which means there is no longer a single truth, individuals began to emphasize awareness of individual rights, appreciate the freedom to express their identity, and the value of individualism increased, as did the development of popular culture. Another factor that may be less realized so far is the role of overly involved parenting which actually makes children only understand one perspective, that they are individuals who have the right to be prioritized. The feeling of being disadvantaged or feeling wronged can serve as the background for why someone becomes entitled. This collective phenomenon needs attention, including the agents or parties and factors that are involved, and what critical and constructive responses can be given, so that we become more aware and responsible citizens in the larger society.